2008
DOI: 10.1007/s10840-008-9290-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dofetilide in patients with atrial fibrillation and atrial flutter

Abstract: Dofetilide is more effective in patients with persistent than in those with paroxysmal AF/AFL. Importantly, short-term response does not necessarily predict long-term efficacy. Significant proarrhythmia can occur even with careful in-hospital monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
4
24
1
Order By: Relevance
“…This observation is consistent with the findings of Banchs and colleagues in a smaller, single center study [9]. One potential explanation for this finding is different mechanisms for maintenance and initiation of atrial arrhythmias, with dofetilide affecting maintenance more than initiation [27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is consistent with the findings of Banchs and colleagues in a smaller, single center study [9]. One potential explanation for this finding is different mechanisms for maintenance and initiation of atrial arrhythmias, with dofetilide affecting maintenance more than initiation [27].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the high rate of pharmacologic conversion observed with dofetilide in our study increases its desirability in the treatment of persistent AF/AFl as pharmacologic conversion obviates the risks associated with anesthesia and direct current cardioversion. kConsistent with previous studies [7,9,11], we found long-term atrial arrhythmia suppression with dofetilide to be modest, with approximately one third of patients remaining arrhythmia free at 1 year. This degree of arrhythmia suppression is comparable to that observed with sotalol [6], flecainide [23], propafenone [24], and dronedarone [25] in long-term follow-up.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Rates of successful CCV with dofetilide have been reported to range from 29%-77% [88,[92][93][94][95], and typically takes ~2 ± 1 doses for conversion [92,93,95], with 21% of patients converting after the first dose of the drug [92]. Multiple studies have noted the rate of chemical cardioversion (CCV) to increase in a dose-dependent manner, the SAFIRE-D trial noted rates of 29.9% for 500 mcg BID, 9.8% for 250 mcg BID and 6.1% for 125 mcg BID [88,93].…”
Section: Dofetilidementioning
confidence: 99%
“…Multiple studies have noted the rate of chemical cardioversion (CCV) to increase in a dose-dependent manner, the SAFIRE-D trial noted rates of 29.9% for 500 mcg BID, 9.8% for 250 mcg BID and 6.1% for 125 mcg BID [88,93]. Dofetilide has been noted to be more effective for CCV in AFL than AF with reported comparisons of 65% vs. 25% [95], and 75% vs. 22% [96].…”
Section: Dofetilidementioning
confidence: 99%